Metastatic Pattern in Triple Negative versus Triple Positive Invasive Ductal Carcinoma of Breast: Single Center Experience - Naznin, Afroza; Yasmin, Farida; Sharmin, Samira; Rahman, Hosne Ara (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Breast carcinoma presents with various subtypes based on expression of hormone receptors for estrogen (ER) and progesterone (PR) and human epidermal growth factor receptor 2 (HER2) gene amplification. This study was planned to gain insight into metastatic behavior of two such immunohistochemical subcategories, namely triple negative and triple positive breast carcinoma. Material & methods: A group of patients with known triple negative breast carcinoma (TNBC) and triple positive breast carcinoma (TPBC) in immunohistochemical analysis were enrolled in the study. Detail history was documented and Technitium-99m MDP skeletal scintigraphy was done. Findings were recorded and finally statistical tests were done using Microsoft Excel and SPSS. Result: About 53.3% of the patients presented with lymph node metastasis, 68.8% of them were triple negative and 31.2% were triple positive. Skeletal and hepatic metastases were found in 25% cases of TPBC group, while history of lung metastasis was documented in 5% cases of TNBC group. Bone scintigraphy revealed positive scan in about 25% subjects of the triple positive group but none of the triple negative group (p value 0.025). Conclusion: TNBC shows propensity for lymph node metastasis, while TPBC tends to metastasize skeletal system. Bangladesh J. Nuclear Med. 28(1): 14-17, 2025